ADVANTAGES OF FIX COMBINATION THERAPY FOR REACHING BLOOD PRESSURE TARGET LEVELS IN PATIENTS WITH ARTERIAL HYPERTENSION (RESULTS OF CLIP-ACCORD PROGRAM) - I. E. Chazova; S. A. Boicov; Yu. A. Karpov; L. G. Ratova; G. P. Artyunov; A. S. Galyavich; R. S. Karpov; O. M. Kislyak; A. I. Martynow; I. V. Medvedeva; V. B. Mychka; O. D. Ostroumova; et al. (Рациональная фармакотерапия в кардиологии)
Information letter of Russian Medical Society of Arterial Hypertension.